Design a Smart Charity Box Based on Line Followers - M Arif Rahman Hakim; Fathan Agil Barra Putra (Indonesian Journal of Electrical Engineering and Electronics, 2023)
The charity box is one of the important tools in the collection of alms funds in mosques in every area. Despite having a significant role in funding, the activities and maintenance of mosques, charity boxes often face a number of problems, such as inefficient manual calculations, risk of theft, and security in the implementation of e-money systems. This article looks at designing a smart charity box that solves these problems. This smart charity box uses the latest technology, including the TCS 34725 color sensor to detect and identify money coming into the charity box. In addition, the charity box is equipped with a line follower system that allows the charity box to move automatically following the flow of worshippers inside the mosque to collect alms. All incoming money data is recorded and calculated automatically, which can be accessed through an application on a smart phone owned by mosque officials. In addition to efficiency in collecting and calculating charity funds, this smart charity box also improves the security of the charity box by integrating a GPS security system and reducing physical contact between pilgrims and charity boxes, which is very relevant to the clean culture implemented from the pandemic period that has passed. Through the integration of technology and innovation, line follower-based smart charity boxes are expected to increase alms fund collection, maintain the security of these funds, and provide comfort to pilgrims in charity.